USING THINK-ALOUD PROTOCOLS METHOD TO IMPROVE RECOUNT TEXT WRITING ACHIEVEMENT OF TENTH GRADE STUDENTS - Sarimarsutalinda Sarimarsutalinda; Rita Inderawati; Lingga Agustina Suganda (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The objectives of this study were to find out: (1) whether or not there was a significant difference in students’ recount text writing achievement between before and after they were taught by using think-aloud protocols method and (2) whether or not there was a significant difference in recount text writing achievement of the students who were taught by using think-aloud protocols method and those who were not. The sample of this study was 60 tenth graders of MA Al-Ittifaqiah Inderalaya who were selected by using a purposive sampling technique. They were divided into control and experimental groups. The data were collected by using writing test which were analyzed by using paired sample and independent sample t-tests. The result of this study showed that there was a significant improvement in the students’ recount text writing achievement of experimental group and, (2) there was a significant difference in recount text writing achievement between the students who were taught by using Think-Aloud protocols method and those who were not. In conclusion, teaching recount text by Think-Aloud protocols method was effective to improve the students’ achievement in writing recount text. Keywords: recount writing acgievement, Think-Aloud protocols method, tenth graders